2019
DOI: 10.3390/rs12010049
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Potential of C-Band SAR in Contributing to Burn Severity Mapping in Tropical Savanna

Abstract: The ability to map burn severity and to understand how it varies as a function of time of year and return frequency is an important tool for landscape management and carbon accounting in tropical savannas. Different indices based on optical satellite imagery are typically used for mapping fire scars and for estimating burn severity. However, cloud cover is a major limitation for analyses using optical data over tropical landscapes. To address this pitfall, we explored the suitability of C-band Synthetic Apertu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 41 publications
0
15
1
Order By: Relevance
“…Although the capacity to detect active fires, especially of VIIRS, can reduce false alarms due to high tree cover, cloud shadows, sensor failures or other reasons [11,31,45], errors are not totally excluded, affecting the number of valid observations [9]. In fact, this can be the main limitation for analyses using optical data, especially in tropical landscapes [8,16,74], as illustrated in Figure 6c, where active deforestation causes high ignition densities resulting in numerous small fires of short duration not detected at a satellite pass [22], or covered by clouds [25,29]. To overcome this latter impediment by cloud obscuration, which is a common limitation to both active fires and also reflectance-based algorithms of even high-resolution optical sensors [5,73], the use of radar technologies for fire detection, potentially useful in areas with permanent cloud cover [5,[74][75][76][77], should be further explored.…”
Section: Discussionmentioning
confidence: 99%
“…Although the capacity to detect active fires, especially of VIIRS, can reduce false alarms due to high tree cover, cloud shadows, sensor failures or other reasons [11,31,45], errors are not totally excluded, affecting the number of valid observations [9]. In fact, this can be the main limitation for analyses using optical data, especially in tropical landscapes [8,16,74], as illustrated in Figure 6c, where active deforestation causes high ignition densities resulting in numerous small fires of short duration not detected at a satellite pass [22], or covered by clouds [25,29]. To overcome this latter impediment by cloud obscuration, which is a common limitation to both active fires and also reflectance-based algorithms of even high-resolution optical sensors [5,73], the use of radar technologies for fire detection, potentially useful in areas with permanent cloud cover [5,[74][75][76][77], should be further explored.…”
Section: Discussionmentioning
confidence: 99%
“…The second index in this study is the Normalized Burn Ratio (NBR) that includes the red and Short Wavelength Infrared (SWIR) 2 band (Formula ( 8)) [72]. The index has been frequently used to study fire severity and for mapping burnt areas [73][74][75][76], but also for forest degradation and recovery analysis [77][78][79].…”
Section: Calculation Of Vegetation Indicesmentioning
confidence: 99%
“…However, mapping fire severity is more challenging than just mapping the occurrence of fire. One major limitation of all optical SRS approaches is the presence of cloud cover that hinders the temporal continuity of the follow-up [325]. For animal movements studies, the severity of a given fire event is more relevant than its frequency and timing alone.…”
Section: Savanna Fire Characterizationmentioning
confidence: 99%
“…To bypass such limitation, SAR images could be used. Philipp and Levick (2020), for example, demonstrated that C-band SAR data can contribute to effectively map fire severity in tropical savanna [325]. Characterizing savanna fire severity in addition of being able to locate fire events could also be useful for measuring more accurately the influence of human land use practices [326] and how it potentially affects animal movements.…”
Section: Savanna Fire Characterizationmentioning
confidence: 99%